2009
DOI: 10.1111/j.1399-5448.2010.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

2010 Consensus Statement on the Worldwide Standardization of the Hemoglobin A1c Measurement

Abstract: Hanas R. and John G. 2010 Consensus Statement on the Worldwide Standardization of the Hemoglobin A1c Measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 10 publications
1
54
0
2
Order By: Relevance
“…On the other hand, there was no significant difference between the nondiabetic and the short-term T1D groups in the frequency of sensor values in the hypoglycemic range, which is particularly striking. In contrast, participants in the longer-term T1D group achieved A1C levels near or within the <7.5% pediatric target range (9) at the expense of a sharp increase in exposure to biochemical hypoglycemia. Using a one-step hyperinsulinemic, hypoglycemic clamp, we have demonstrated that 56% of the subjects in the short-term group maintained a glucagon response to hypoglycemia, which may have contributed to their low incidence of biochemical hypoglycemia (10).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, there was no significant difference between the nondiabetic and the short-term T1D groups in the frequency of sensor values in the hypoglycemic range, which is particularly striking. In contrast, participants in the longer-term T1D group achieved A1C levels near or within the <7.5% pediatric target range (9) at the expense of a sharp increase in exposure to biochemical hypoglycemia. Using a one-step hyperinsulinemic, hypoglycemic clamp, we have demonstrated that 56% of the subjects in the short-term group maintained a glucagon response to hypoglycemia, which may have contributed to their low incidence of biochemical hypoglycemia (10).…”
Section: Discussionmentioning
confidence: 98%
“…Data on HbA1c are derived from capillary blood samples taken in connection with visits to the diabetes center. The International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) reference method is used in Sweden, and HbA1c values are presented both as IFCC (mmol/mol) and as NGSP/DCCT (%) …”
Section: Methodsmentioning
confidence: 99%
“…In NDR all available values were used for the mean HbA1c value. The IFCC reference method has been adopted in Sweden, and HbA1c values will be presented both as NGSP/DCCT (%) and as IFCC (mmol/mol). For example, 58 mmol/mol (IFFC) corresponds to 7.5% (NGSP/DCCT), 10 mmol/mol is about 0.9%.…”
Section: Methodsmentioning
confidence: 99%